Intersectional feminist criminology: A critical companion to theory and research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice. Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic. Critical perspectives on the topic. Critical thinking breaks. Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system. © 2025 by Venezia Michalsen. All rights reserved.
Keywords: dept.soc

Reentry court judges: the key to the court - Salvatore, Christopher, Venezia, Michalsen; Taylor, Caitlin (Journal of Offender Rehabilitation, 2020)
Over the last few decades, treatment-oriented court judges have moved away from being neutral arbitrators in an adversarial court process to treatment facilitators. In the problem-solving court model, judges are part of a more therapeutic treatment process with program participants and a courtroom work group. The shift from the use of the traditional criminal justice process toward the use of more treatment-oriented models for some populations highlights the need to systematically document key elements of treatment court models. In particular, it is important to clearly document the role of Reentry Court Judges because they are a key component of the Reentry Court model. The current study used interviews with members of the courtroom work group, as well as a focus group interview of former participants in the program, to help identify the role of the judge and activities the judge engages. Findings revealed that the judges played a supportive, informal role, balanced with a more formal, authoritarian role, and the judges engaged participants in pre-court meetings, as well as courtroom sessions. Further, the judges facilitated interactions with program participants outside the courtroom, demonstrating that the judge is a core component of success for participants in Reentry Court.
_eprint: https://doi.org/10.1080/10509674.2020.1733164
Keywords: dept.soc; judges; peer-reviewed; probationers; reentry; reintegration; treatment

Positive Mood and the Perception of Variability Within and Between Groups - Stroessner, Steven J.; Mackie, Diane M.; Michalsen, Venezia (Group Processes & Intergroup Relations, 2005)
Three experiments investigated the effects of positive mood on perceptions of variability within and between groups. Participants formed impressions of two different and highly variable groups under a neutral or positive mood. When participants expected to learn about both groups, positive mood increased perceived intergroup similarity but did not affect perceived intragroup variability. In contrast, when participants expected to learn about only one group, judgments of intergroup and intragroup similarity were both affected by mood. Mood and the intergroup context influenced the nature and degree of information processing and resultant judgments of variability in social groups.
Keywords: dept.soc; peer-reviewed

Not All Women Are Mothers: Addressing the Invisibility of Women Under the Control of the Criminal Justice System Who Do Not Have Children - Michalsen, Venezia; Flavin, Jeanne (The Prison Journal, 2014)
Research has consistently shown that most women under the control of the criminal justice system are mothers. The robustness of this finding has been accompanied by a failure to consider the characteristics and needs of women without children. In this study, we examine data on 1,334 formerly incarcerated women. Findings indicate that while mothers and non-mothers share some characteristics, they differ on several others, most notably demographic profile, mental health, and timing of contacts with the criminal justice system. These results suggest a need to recognize the diversity among women offender groups, particularly when developing policies and programs need.
Keywords: dept.soc; peer-reviewed

More than Visiting Hours: Maintaining Ties Between Incarcerated Mothers and Their Children - Michalsen, Venezia; Flavin, Jeanne; Krupat, Tanya (Sociology Compass, 2010)
The majority of people in America’s prisons are the parents of minor children. Incarcerated mothers, in particular, were likely to have been a part of their children’s lives before their imprisonment, and most will soon be returning to the community and to their children. Research has shown that it is in the best interests of the mothers and the children to maintain a relationship across the prison bars. In this article, we use the example of New York State to show how institutional policies and structures can impede or encourage efforts to maintain ties between women and their children and why demonstrating support for family ties must extend well beyond having visiting hours.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1751-9020.2010.00291.x
Keywords: dept.soc; peer-reviewed

Abolitionist Feminism as Prisons Close: Fighting the Racist and Misogynist Surveillance “Child Welfare” System - Michalsen, Venezia (The Prison Journal, 2019)
The global prison industrial complex was built on Black and brown women’s bodies. This economy will not voluntarily loosen its hold on the bodies that feed it. White carceral feminists traditionally encourage State punishment, while anti-carceral, intersectional feminism recognizes that it empowers an ineffective and racist system. In fact, it is built on the criminalization of women’s survival strategies, creating a “victimization to prison pipeline.” But prisons are not the root of the problem; rather, they are a manifestation of the over-policing of Black women’s bodies, poverty, and motherhood. Such State surveillance will continue unless we disrupt these powerful systems both inside and outside prisons.
Keywords: dept.soc; peer-reviewed

Mothering and Desistance in Re-Entry - Michalsen, Venezia (Routledge, 2018)
Although there is plentiful research on the impact of marriage, employment and the military on desistance from criminal behaviour in the lives of men, far less
Keywords: dept.soc

A Cell of One’s Own? Incarceration and Other Turning Points in Women’s Journeys to Desistance - Michalsen, Venezia (International Journal of Offender Therapy and Comparative Criminology, 2019)
Research has shown the importance of turning points in desistance from criminal behavior. Using qualitative data from a sample of 100 formerly incarcerated mothers interviewed about their criminal behavior, this article explores their descriptions of transition moments and whether and how those moments affected their criminal behavior. The findings indicate that whereas parenting emerges as a turning point, the practical difficulties of reentry may reduce the impact of mothering on women’s desistance. More self-focused turning points, such as those due to incarceration, arrest, and sobriety appeared to be particularly important to the women’s desistance. This article emphasizes the need for research into the subjective and environmental factors that affect women’s desistance behaviors.
Keywords: dept.soc; peer-reviewed

Trigger Warnings: From Panic to Data - Laguardia, Francesca; Michalsen, Venezia; Rider-Milkovich, Holly (Journal of Legal Education, 2017)
Keywords: dept.soc; peer-reviewed

Mothering as a Life Course Transition: Do Women Go Straight for Their Children? - Michalsen, Venezia (Journal of Offender Rehabilitation, 2011)
In this study, qualitative, in-depth interviews were conducted with 100 formerly incarcerated mothers to explore the relationship between attachment to children and desistance from criminal behavior. Exploratory data analysis revealed that mothers do believe that children play important roles in their desistance, consistent with the tenets of life course theory. However, children were also described as sources of great stress, which may in turn promote criminal behavior. Women also related desistance to reliance on self and a higher power, and to a desire to avoid future involvement with the criminal justice system. The article concludes with a call for more research on women's desistance, and increased consideration of parent–child relationships in corrections policy decision making.
_eprint: https://doi.org/10.1080/10509674.2011.589887
Keywords: attachment; children; dept.soc; desistance; life course theory; mothers; peer-reviewed; reentry

Are Suicide Attempters Who Self-Mutilate a Unique Population? - Stanley, Barbara; Gameroff, Marc J.; Michalsen, Venezia; Mann, J. John (American Journal of Psychiatry, 2001)
OBJECTIVE: Individuals who mutilate themselves are at greater risk for suicidal behavior. Clinically, however, there is a perception that the suicide attempts of self-mutilators are motivated by the desire for attention rather than by a genuine wish to die. The purpose of this study was to determine differences between suicide attempters with and without a history of self-mutilation. METHOD: The authors examined demographic characteristics, psychopathology, objective and perceived lethality of suicide attempts, and perceptions of their suicidal behavior in 30 suicide attempters with cluster B personality disorders who had a history of self-mutilation and a matched group of 23 suicide attempters with cluster B personality disorders who had no history of self-mutilation. RESULTS: The two groups did not differ in the objective lethality of their attempts, but their perceptions of the attempts differed. Self-mutilators perceived their suicide attempts as less lethal, with a greater likelihood of rescue and with less certainty of death. In addition, suicide attempters with a history of self-mutilation had significantly higher levels of depression, hopelessness, aggression, anxiety, impulsivity, and suicide ideation. They exhibited more behaviors consistent with borderline personality disorder and were more likely to have a history of childhood abuse. Self-mutilators had more persistent suicide ideation, and their pattern for suicide was similar to their pattern for self-mutilation, which was characterized by chronic urges to injure themselves. CONCLUSIONS: Suicide attempters with cluster B personality disorders who have a history of self-mutilation tend to be more depressed, anxious, and impulsive, and they also tend to underestimate the lethality of their suicide attempts. Therefore, clinicians may be unintentionally misled in assessing the suicide risk of self-mutilators as less serious than it is.
Keywords: dept.soc; peer-reviewed

Intersectional Feminist Criminology: A Critical Companion to Theory and Research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice. Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic Critical perspectives on the topic Critical thinking breaks Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system.
Keywords: dept.soc

“I'm Not Good Enough for Anyone”: Legal Status and the Dating Lives of Undocumented Young Adults - Pila, Daniela (Sociological Forum, 2016)
The impact of legal status on romantic relationships has not been adequately explored in the literature. Based on video and phone interviews with 25 undocumented activists from the ages of 18 to 28 years old, this research examines how legal status affects the romantic relationships of undocumented women and men. The hegemony of traditional dating scripts made it difficult for those without legal status to participate. Gender roles were consistent with stereotypical male and female roles in dating, which often attribute more power and responsibility to men. As such, women experienced a slight advantage because traditional notions of courtship did not require them to provide the resources required for dating, such as money or transportation, which in contrast were commonly expected of the men. In contrast, women noted the difficulties of disclosing their legal status and depending on their partners for everyday activities. Additionally, both men and women faced exclusion that inhibited their dating lives, as a direct result of their legal status. This suggests that the impact of legal status may be salient at all stages of family formation and that undocumented young adults are experiencing a distinct phenomenon compared to their documented and native-born peers.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/socf.12237
Keywords: citizenship; dating; dept.soc; immigration; legality; undocumented; young adults

Relocation as an Adaptation to Sea-Level Rise: Valuable Lessons from the Narikoso Village Relocation Project in Fiji. - Bertana, Amanda (Case Studies in the Environment, 2019)
Keywords: dept.soc

Invisible Mothers: Unseen yet Hypervisible After Incarceration. By Garcia-HallettJanet (University of California Press, 2022, 248pp. £30.00) - Michalsen, Venezia (The British Journal of Criminology, 2023)
Invisible Mothers: Unseen yet Hypervisible After Incarceration, the new book by Dr. Janet Garcia-Hallett, has almost innumerable contributions to the field. The first thing that the reader will likely notice that makes this work stand out is the impact of Garcia-Hallett’s positionality as an Afro-Latina mother on the holistic understanding of the experiences of the Black and brown women as mothers and victims of the racist American carceral system. Garcia-Hallett grew up in Harlem, witnessing the transformation of her community due to the takeover of the penal system. For this book, she interviewed 37 mothers in New York City with histories of incarceration, and her writing skilfully puts the reader in her shoes as she presents the findings from her interviews, which took place in their kitchens, booths in McDonald’s, and at tables in shelters. In her exploration of these women’s experiences, Garcia-Hallett departs from the traditional pitiful exploration of their lives, but instead, paints a complicated, multifaceted picture of women engaging actively in many different types of motherwork, while facing almost constant obstacles from racist and misogynist criminal legal and child welfare systems that criminalize, pathologize and penalize their survival of their marginalization, rather than helping ‘save’ children and their mothers. She provides a critical and structural analysis while also introducing each woman as deeply unique in her strengths and challenges and is able to acknowledge the importance of the children without letting them overshadow the mothers. This is no small feat.
Keywords: book.review; dept.soc

Organizational scaffolding for climate adaptation: how intermediaries manage evaluative tensions - Wissman, Nichole Kay; Bertana, Amanda; Manning, Stephan Davys (Academy of Management Proceedings, 2023)
The grand challenge of preparing for climate impacts through climate adaptation relies on intermediaries, including local NGOs, consulting firms, and government agencies. Climate adaptation elicits evaluative tensions coming from what we call the dual organizational complexity. The dual organizational complexity includes evaluation ambiguity in (1) the interconnectedness and co-evolutionary dynamics of locally bounded social and ecological systems and (2) an increasingly complex network of interconnected organizations, including a diverse set of public, private, and semi-private actors who provide funding, market power, and expertise. We find that intermediaries address evaluative tensions through organizational scaffolding or building socio-material infrastructures that can support resilience and increase evaluative and adaptive capacity for future projects, albeit imperfectly. Importantly, we argue that climate adaptation needs facilitators with the capacity to connect very localized bottom-up needs to top-down resources in a continuous cycle of resource allocation, communication, and accountability, especially in the face of the increasing organizational complexity involved.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Organizations and the Natural Environment; dept.soc

The role of power in community participation: Relocation as climate change adaptation in Fiji - Bertana, Amanda (Environment and Planning C: Politics and Space, 2020)
As the impacts of climate change intensify, potential relocation is becoming more of a reality for coastal communities throughout the world. This is furthering the demand for the implementation of governance relocation frameworks. In order to stay true to the principles of environmental justice while at the same time ensuring an effective policy that meets the needs and wants of affected communities, an adaptive relocation framework requires collaboration between state and non-state actors. It is thus important to pay attention to how non-state actors are incorporated into public participatory climate change adaptation efforts. In order to affectively address previous limitations of public participation, stakeholders must pay attention to already existing power systems. Through a case study approach of a village relocation project in Fiji, I examine the role of power in a climate change adaptation plan that involved the community of Vunidogoloa, local government, and national government stakeholders. I employ Steven Lukes’s three-dimensional framework of power to the case of Vunidogoloa, a Fijian village that relocated inland due to coastal erosion and shoreline flooding, to illustrate how the political arrangement of participation reinforced existing hierarchies between the village and the government.
15 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed

Religious Explanations for Environmental Degradation in Narikoso, Fiji - Bertana, Amanda (Understanding Climate Change through Religious Lifeworlds, 2021)
How can religion help to understand and contend with the challenges of climate change?Understanding Climate Change through Religious Lifeworld,edited by David Haberman, presents a unique collection of essays that detail how the effects of human-related climate change are actively reshaping religious ideas and practices, even as religious groups and communities endeavor to bring their traditions to bear on mounting climate challenges.People of faith from the low-lying islands of the South Pacific to the glacial regions of the Himalayas are influencing how their communities understand earthly problems and develop meaningful responses to them. This collection focuses on a variety of different aspects of this critical interaction, including the role of religion in ongoing debates about climate change, religious sources of environmental knowledge and how this knowledge informs community responses to climate change, and the ways that climate change is in turn driving religious change.Understanding Climate Change through Religious Lifeworlds offers a transnational view of how religion reconciles the concepts of the global and the local and influences the challenges of climate change.
Keywords: dept.soc

Breaking wind: A comparison between U.S. and European approaches in offshore wind energy leadership in the North Atlantic region - Gallaher, Adam; Graziano, Marcello; Axon, Stephen; Bertana, Amanda (Renewable and Sustainable Energy Reviews, 2023)
The United States has only recently begun investing in commercial-scale offshore wind energy (OWE). Although the United States is slow to progress, it is uniquely positioned to build on the existing knowledge that coastal European countries have applied for their own energy transitions. In this study, we analyze how federal and regional plans for expanding the OWE sector in the United States brought to the surface decade-long tensions related to multi-scale governance mismatches, jurisdictional conflicts, and unclear pathways for implementing national industrial policies. Drawing upon the European experience with OWE, we employ a dynamic multi-level perspective framework enriched by socio-ecological elements to examine the United States energy transition through its most promising technology. From our framework we identify six categories of OWE developments characterized by both unique and shared elements between the United States and European coastal countries. These elements are: (1) role of local communities, (2) governance structures, (3) multi-scale government interactions, (4) regional socioeconomic structures, (5) socio-ecological impacts, and (6) relationships with existing industries. Drawing upon our analysis, we identify and conceptually map four research areas in need of further development for the United States and the research community— (1) knowledge, (2) potential, (3) adaptation, and (4) learning. These insights provide critical information to ensure that the United States expansion into offshore energy generation is characterized by elements of justice, equity, and inclusive regional economic development.
0 citations (Crossref) [2023-10-31]
Keywords: Blue economy; Comparative analysis; Just energy transitions; Multi-level perspective; Offshore wind energy; dept.egm; dept.soc; peer-reviewed

Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Education - Meyerhoffer, Cassi A.; Rodriguez, Brittany Leigh (University of Georgia Press, 2023)
Over the last several years, the United States has experienced a surge in bystander videos that have captured incidents of police brutality and prejudice directed largely at Black people. Public outrage surrounding police brutality persists as these incidents continue to reach the public eye. As public discourse around police brutality and racial inequality largely centers on specific events, there is a dearth of information about systemic racism and how race and racism pervade every single aspect of American life. How Black people are often treated by law enforcement is reflective of larger historical racial inequities and injustices that extend far beyond the criminal justice system and intersect with how Black people access housing, occupy public spaces, and are treated in American public schools.Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Educationfocuses on contemporary systemic racism as it relates to how the U.S. criminal justice system, housing system, and education system intersect to create a matrix of inequality for Black people. To illustrate the systemic nature of racism in American policing and communities, this book highlights contemporary policies and practices that intersect with residential segregation and public schooling that continue to affect Black people on a large-scale, structural level―demonstrating the extent to which the United States criminal justice system is tied to where people live and how they are treated and educated in public schools.
Keywords: dept.soc

Curriculum Innovation Program Fellowship "Serving the Community Through Service Learning" - Jackson, Shirley A. (2011)
Dr. Jackson worked on her Curriculum Innovation Program fellowship, "Serving the community through service learning," completed write-up for Ethnic Studies Curriculum-Related Activity Grant for "Ethnic Studies Program Development at Southern Connecticut State University," worked on several articles and two book proposals encompassing research of race issues and their representation in contemporary cartoons, as well as attended conferences, both as a presenter and a chair, participated in workshops, and reviewed textbook chapters and an article.
Keywords: SCSU; Sabbatical leave report; dept.soc; faculty_collection; sabbatical_report

Exploring the Links Between Student Learning and Instructor/Course Evaluation. - Polka, Joseph A. (2006)
Keywords: dept.soc; faculty_collection; sabbatical_report

Student Retention/Attrition. - Polka, Joseph (1998)
Keywords: dept.soc; faculty_collection; sabbatical_report

The Social Charcteristics of Recent Graduated of Irish Universities Who Emigrate for Overseas Employment. - Ryan, Michael (1991)
Keywords: dept.soc; faculty_collection; sabbatical_report

History of American Women's Resistance to War: Anthology of Writings. - McCarthy, Katherine (1990)
Keywords: dept.soc; faculty_collection; sabbatical_report

Racism in the United States. - Doob, Christopher Bates (1988)
Keywords: dept.soc; faculty_collection; sabbatical_report

Social Problems - Doob, Christopher Bates (Harcourt Brace College Publishers, 1995)
[This book] focus[es] on topics [such as:] the corporate state, an emphasis on the impact of the power elite in a capitalist state; the environment, pollution and depletion of resources, with a new sense of urgency created for alleviating if not solving these chronic problems; urban deterioration, the steady decline in the physical and cultural quality of city life, with little successful effort to plan cities with citizens' basic needs and interests in mind; racism, the legacy of our nation's racist past carrying into the present and still impacting heavily on many citizens, most notably the minority poor; sexism, men's traditional domination of women ... youth problems, a variety of major difficulties facing many young people [and] crime, an analysis of some of the most disturbing, damaging types of crime ravaging the modern United States. These subjects are examined in depth, with diverse, primarily recent source material used. -Pref.
Keywords: Social problems; Sociology; dept.soc; faculty_collection

The Loveless Family: Getting Past Estrangement and Learning How to Love - Bloch, Jon P. (Praeger, 2011)
This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was "dysfunctional" or not., This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was ""dysfunctional"" or not.
Keywords: Families; Psychological aspects; Parenting; Dysfunctional families; Adult children of dysfunctional families; Love; dept.soc; faculty_collection

Race: Readings on Identity, Ideology, and Inequality - Meyerhoffer, Cassi (Cognella, 2021)
Keywords: Race awareness; Race relations; United States; Racism; United States; United States; dept.soc; faculty_collection

Ph.Dead - Bloch, Jon P. (Pegasus Books, 2016)
Keywords: College stories; dept.soc; faculty_collection

Identity Thief - Bloch, Jon P. (Bacon Press Books, 2014)
Keywords: Fiction; Identity theft; dept.soc; faculty_collection

Social Inequality and Social Stratification in US Society - Doob, Christopher Bates (Pearson, 2013)
Keywords: Equality; United States; United States; Social stratification; dept.soc; faculty_collection

Narcotic Addicts in Ukraine: Exploring Social Correlates of Addiction - Adams, Gregory A. (LAP Lambert, 2012)
Keywords: Drug addiction; Ukraine; dept.soc; faculty_collection

German Professionals in the United States a Gendered Analysis of the Migration Decision of Highly Skilled Families - Eich-Krohm, Astrid (LFB Scholarly Pub., 2012)
Keywords: Emigration and immigration; Foreign workers; German; Germany; Immigrants; Germany; Professional employees; Social aspects; Social aspects; United States; Social conditions; Germany; United States; United States; Brain drain; United States; Professional employees; dept.soc; faculty_collection

Democracy Deferred: Civic Leadership After 9/11 - Woods, David W. (Palgrave Macmillan, 2012)
Keywords: 21st century; Civics; 21st century; September 11 Terrorist Attacks; 2001; History; Influence; Political participation; United States; dept.soc; faculty_collection

Race, Ethnicity, and the American Urban Mainstream - Doob, Christopher Bates (Pearson/Allyn and Bacon, 2005)
"Race, Ethnicity, and the American Urban Mainstream uses history, biography, and sociological analysis to examine the achievements and struggles of racial and ethnic groups in American cities. This text is organized around social systems (politics, housing, education, economics, and work) rather than groups or concepts such as prejudice and discrimination. A group of in-depth profiles of minority communities, in cities such as Oakland, Detroit, Los Angeles, and Chicago, help to illustrate major concepts."–BOOK JACKET.
Keywords: Canada; United States; Ethnic relations; Ethnic relations; United States; Race relations; United States; Social conditions; Canada; Social conditions; Racism; United States; United States; City and town life; United States; Cultural pluralism; Urban minorities; dept.soc; faculty_collection

Murder by Design - Bloch, Jon P. (St. Martin's Minotaur, 2004)
Opting to have his home remodeled on a popular cable reality show, celebrity gossip columnist Rick Domino is horrified when the consulting designer is found brutally murdered, a case for which Rick teams up with unstylish but attractive police detective Terry Zane.
Keywords: Crimes against; Fiction; Fiction; Hollywood (Los Angeles; Calif.); Fiction; Interior decorators; Fiction; Television programs; Gossip columnists; dept.soc; faculty_collection

Justice for the Poor: A Study of Criminal Defense Work - Emmelman, Debra S. (Ashgate, 2003)
Keywords: Public defenders; United States; United States; Criminal justice; Administration of; United States; Legal assistance to the poor; United States; Plea bargaining; dept.soc; faculty_collection

Best Murder of the Year - Bloch, Jon P. (St. Martin's Minotaur, 2002)
Gossip columnist Rick Domino is stunned when his lover, actor Shane Kirk, wins an Oscar for Best Actor but is nowhere to be found, and when Rick finally finds Shane, who is holding a gun and a dead body, Shane takes off, leaving Rick to face the police.
Keywords: Academy Awards (Motion pictures); Fiction; Fiction; Gay men; Fiction; Gossip columnists; Fiction; Hollywood (Los Angeles; Calif.); Fiction; Motion picture industry; dept.soc; faculty_collection

An Ethnographic Study of an American Conservative Synagogue - Laskin, Martin (E. Mellen Press, 2002)
Keywords: Connecticut; Hamden; History; Liturgy; Jews; Sociological aspects; Conservative Judaism; Temple Beth Shalom (Hamden; Conn.); Synagogues; dept.soc; faculty_collection

Finding Your Leading Man: How to Create Male-to-Male Intimacy and Make Your Relationship a Blockbuster - Bloch, Jon P. (St. Martin's Griffin, 2000)
Keywords: Gay men; Interpersonal relations; Intimacy (Psychology); dept.soc; faculty_collection

Sociology: An Introduction - Doob, Christopher Bates; Faupel, Charles E. (Harcourt Press, 2000)
Keywords: Sociology; dept.soc; faculty_collection

Justice for the Poor: A Case Study of Criminal Defense Work. - Emmelman, Debra S. (Fall; Sociology/Anthropology., 2000)
Keywords: dept.soc

New Spirituality, Self, and Belonging: How New Agers and Neo-Pagans Talk About Themselves - Bloch, Jon P. (Praeger, 1998)
Keywords: Case studies; Neopagans; Case studies; New Age movement; Interviews; Interviews; Neopagans; New Age persons; Psychology; Social aspects; Neopaganism; Social aspects; New Age persons; dept.soc; faculty_collection

Racism: An American Cauldron - Doob, Christopher Bates (HarperCollinsCollege, 1996)
Keywords: Race relations; Racism; United States; United States; dept.soc; faculty_collection

Sociology: An Introduction - Doob, Christopher Bates (Holt, Rinehart and Winston, 1988)
Keywords: Sociology; dept.soc; faculty_collection

Sociology: An Introduction - Doob, Christopher Bates (Holt, Rinehart, and Winston, 1985)
Keywords: Sociology; dept.soc; faculty_collection

Systems and Processes; Collected Works in Sociology. - Reda, Mario A.; Fappiano, Eugene; Czikowsky, Leon (College & University Press, 1968)
Keywords: Sociology; dept.soc; faculty_collection

Climate change adaptation, gender, and mainstreaming: the role of gender in Fiji's relocation initiative - Bertana, Amanda; Blanton, Natalie (Climate and Development, 2022)
Climate change has elucidated already existing gender inequalities associated with unequal access to resources, decision-making processes, and higher exposure to environmental shocks and stressors. Growing acknowledgment of the gender-differentiated implications of climate change in recent years has placed gender equality as a focal point in international discourses on climate change adaptation. The policy perspective of gender equality is universalized, but how it transcribes in local climate change adaptation projects remains elusive. Using the relocation of Vunidogoloa, Fiji, this article explores the tension and compatibility between the way gender equality is discussed and how it is implemented in climate change adaptation projects.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/17565529.2022.2055524
Keywords: Climate change; Fiji; adaptation; dept.soc; gender equality; gender mainstreaming; peer-reviewed; relocation; sea level rise

Beyond maladaptation: structural barriers to successful adaptation - Bertana, Amanda; Clark, Brett; Benney, Tabitha M.; Quackenbush, Cameron (Environmental Sociology, 2022)
Around the world adaptation projects are being implemented, with the hope of essentially climate proofing communities. While there is an abundance of failed adaptation schemes in developing and developed countries alike, there has been little scholarship on this problem. Through interviews with twenty-two climate change adaptation practitioners, we identify four structural challenges that contribute to maladaptation: the focus on technological fixes versus holistic approaches; the difficultly of distinguishing between adaptation and development; the problem of quantifying non-quantifiable variables; and the existence of competing problems given that failure to mainstream climate change adaptation. Addressing these maladaptation dynamics is necessary to enhance successful adaptation processes.
4 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/23251042.2022.2068224 SCSU Faculty Scholar Award
Keywords: SCSU Faculty Scholar Award; award_winner; climate change; climate change adaptation; dept.soc; development; maladaptation; peer-reviewed; policy

The Open Covenant: Social Change in Contemporary Society - Doob, Christopher Bates (Praeger, 1987)
Keywords: Elite (Social sciences); Social conditions; United States; Social change; United States; United States; Social movements; dept.soc; faculty_collection

Racism: An American Cauldron - Doob, Christopher Bates (Longman, 1999)
Keywords: Race relations; Racism; United States; United States; dept.soc; faculty_collection

Sociology: An Introduction - Doob, Christopher Bates (Harcourt Press, 1997)
Keywords: Sociology; dept.soc; faculty_collection

The Anatomy of Competition in Sports: The Struggle for Success in Major US Professional Leagues - Doob, Christopher Bates (Rowman & Littlefield, 2015)
Keywords: Professional sports; Psychology; Competition (Psychology); Success; United States; Athletes; dept.soc; faculty_collection

Great Expectations: The Sociology of Survival and Success in Organized Team Sports - Doob, Christopher B. (Routledge, 2018)
Keywords: dept.soc

Poverty, Racism, & Sexism: The Reality of Oppression in America - Doob, Christopher Bates (Routledge, Taylor & Francis Group, 2021)
"Exploring the structural causes and consequences of inequalities based on a person's race, class, and gender, Poverty, Racism & Sexism: The Reality of Oppression in America concentrates on this formidable set of disadvantages, demonstrating how Americans are adversely affected by just one or a combination of three social factors. Grounded in sociological thought, the text highlights unfolding stories about major social inequalities and relentless campaigns for people's rights. Weaving together such concepts as individualism, social reproduction, social class, and intersectionality, the book provides a framework for readers to understand the vast injustices these groups encounter, where and why they originated, and why they continue to endure. Poverty, Racism & Sexism is a compact, versatile volume which will prove an invaluable resource for those studying social inequality, social problems, social stratification, contemporary American society, social change, urban sociology, and poverty and inequality"–
Keywords: Equality; Race relations; United States; Poverty; United States; Racism; United States; Sexism; United States; United States; dept.soc; faculty_collection

Twenty-first-century trends in highly skilled migration - Eich-Krohm, A. (Routledge International Handbook of Migration Studies, 2013)
Journal Abbreviation: Routl. Int. Handb. of Migration Stu.
Keywords: dept.soc

Conclusion: Contemporary trends in the intersection of race, class, and gender - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Conversations on race, class, and gender - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Cultural contexts and identity - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and education - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and migration - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and sexualities - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and work - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Routledge international handbook of race, class, and gender - Jackson, S.A. (Taylor and Francis, 2014)
The Routledge International Handbook of Race, Class, and Gender chronicles the development, growth, history, impact, and future direction of race, gender, and class studies from a multidisciplinary perspective. The research in this subfield has been wide-ranging, including works in sociology, gender studies, anthropology, political science, social policy, history, and public health. As a result, the interdisciplinary nature of race, gender, and class and its ability to reach a large audience has been part of its appeal. The Handbook provides clear and informative essays by experts from a variety of disciplines, addressing the diverse and broad-based impact of race, gender, and class studies. The Handbookis aimed at undergraduate and graduate students who are looking for a basic history, overview of key themes, and future directions for the study of the intersection of race, class, and gender. Scholars new to the area will also find the Handbook’s approach useful. The areas covered and the accompanying references will provide readers with extensive opportunities to engage in future research in the area. © 2015 Shirley A. Jackson.
Journal Abbreviation: Routledge International Handb. of Race, Class, and Gend. Pages: 277 Publication Title: Routledge International Handb. of Race, Class, and Gend.
Keywords: dept.soc

Theorizing race, class, and gender studies - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

When enough is enough: African american women reclaiming themselves - Jackson, S.A. (Letting Go: Feminist and Social Justice Insight and Activism, 2015)
Journal Abbreviation: Letting Go: Feminist and Soc. Justice Insight and Activism
Keywords: dept.soc

Justice for the Poor: A Study of Criminal Defence Work - Emmelman, D.S. (Taylor and Francis, 2018)
This title was first published in 2003. In this study, the author examines the behavior of one group of court-appointed defence attorneys and reaches the conclusion that although, in contrast to popular opinion, these attorneys maintain an adversarial stance against the prosecutors and behave in a legally ethical (or "procedurally just") manner, case outcomes are unduly shaped by social class and are therefore substantively unjust. This occurs because poor defendants typically lack cultural rhetoric that favourably influences those who construct and operate the criminal court system. Ironically, this indicates that, in many cases, the process of plea bargaining may be more substantively just than trials. A major contribution of the study is the detailed analysis of the manner by which oppression and substantive injustice occur in the adjudication of many cases and how the cultural practices of the powerful can frequently misconstrue, exclude and mute the voices of the poor. © Debra S. Emmelman 2003.
Journal Abbreviation: Justice for the Poor: A Study of Criminal Def. Work Pages: 153 Publication Title: Justice for the Poor: A Study of Criminal Def. Work
Keywords: dept.soc

Belarus at the United Nations: An analysis of Belarus's global policy alignment following the Maidan revolution in Ukraine - Lennon, O.; Becker, A. (Demokratizatsiya, 2019)
Since the fall of the Soviet Union, Belarus has been the slowest of the countries in Eastern Europe to shake off its authoritarian past and ties with Russia. However, the Maidan revolution in Ukraine and Russia's subsequent annexation of Crimea and occupation of parts of Eastern Ukraine in 2014 might have forced Belarus's president, Aleksander Lukashenka, to start questioning the terms of this relationship. Russia's violation of Ukraine's sovereignty created a much more real possibility-and fear-that, if push came to shove, Russia would not hesitate to act similarly toward Belarus. Belarus's political choices are hard to predict: will it remain a dictatorship in Russia's shadow or will it embrace democracy and the rule of law and seek closer integration with the West? This study examines Belarus's global policy alignment from 2007 to 2017 by analyzing its voting patterns on contested issues-those on which Russia's and the U.S.'s votes diverged-at the United Nations General Assembly. While Belarus seems to have been disassociating itself from Russia on some global issues, as evidenced by its voting record at the UN General Assembly, and its democracy level increased from 2014-2016, there is insufficient evidence to believe that Belarus might in fact be aligning more with the West and moving away from Russia. While Belarus's diplomatic pendulum has increasingly swung toward the US, it has inevitably bounced back to its "home base"-Russia. © 2019 Heldref Publications. All rights reserved.
Keywords: Belarus; Crimea; Russian Federation; Ukraine; United Nations; authoritarianism; democracy; dept.soc; diplomatic relations; international relations; peer-reviewed; policy approach; sovereignty; voting behavior; ⛔ No DOI found

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
3 citations (Crossref) [2023-10-31] tex.coden: GGJOA tex.document_type: Article tex.source: Scopus
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed

“On the street, the only person you gotta bow down to is yourself”: Masculinity, homelessness, and incarceration - Umamaheswar, Janani (Justice Quarterly, 2021)
Despite the well-established link between homelessness and incarceration, very little qualitative research has focused on the social processes that underlie this nexus. In this article, I draw on 19 in-depth interviews with incarcerated men who reported pre-prison housing instability, supplemented with 5 interviews with formerly-incarcerated men experiencing homelessness, to explore the gendered nature of the homelessness-incarceration nexus. I propose the concept of “liberative instability”—defined as an unfettered lifestyle characterized by double-edged freedom and independence—to explore the changing meaning of homelessness in men’s narratives of their life course. Additionally, I explore how themes of masculinity and liberative instability are embedded in men’s narratives of freedom and confinement as they reflect on their experiences with homelessness and incarceration. These findings animate existing quantitative research by highlighting that the homelessness-incarceration nexus cannot be understood fully or disrupted without considering the significance of age-graded cultural scripts regarding masculinity. © 2021 Academy of Criminal Justice Sciences.
1 citations (Crossref) [2023-10-31]
Keywords: Homelessness; dept.soc; incarceration; masculinity; peer-reviewed; the life course

Book Review: Superpredators: The Demonization of Our Children by the Law, by Peter Elikann, Perseus Publishing, 1999. - Kenty, Jessica L. (Bimonthly Review of Law Books, 2000)
Keywords: book.review; dept.soc; ⛔ No DOI found

Connecticut - Kenty-Drane, Jessica L.; Prince-Stewart, Jamilah (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Google-Books-ID: xw5zAwAAQBAJ
Keywords: dept.soc

Wealth and education - Kenty-Drane, Jessica L. (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Google-Books-ID: xw5zAwAAQBAJ
Keywords: dept.soc

Early Isolation: Racial and Economic Segregation in U.S. Public Elementary Schools - Kenty-Drane, Jessica L. (Race, Gender & Class, 2009)
The literature shows that racially and economically segregated schools diminish educational outcomes for students in non white schools with impoverished peers (Frankenberg & Lee, 2002; Mayer, 2000). To reveal which children are apt to begin their education in high minority and poor schools, this study drew on nationally representative data from the Early Childhood Longitudinal Study. Evidence documents variations in school racial and economic contexts according to children's race and social class backgrounds. Over half of Black and Hispanic first-graders attend segregated minority and poor schools while very few White first-graders do so. Additional analyses reveal that while social class is a useful predictor of educational segregation, it is less predictive for Black and Asian students than for White and Hispanic students.
Keywords: dept.soc; ⛔ No DOI found

The racial wealth gap - Shapiro, Thomas M.; Kenty-Drane, Jessica L. (African Americans in the U.S. Economy, 2005)
Over the last several decades, academic discourse on racial inequality has focused primarily on political and social issues with significantly less attention on the complex interplay between race and economics. African Americans in the U.S. Economy represents a contribution to recent scholarship that seeks to lessen this imbalance. This book builds upon, and significantly extends, the principles, terminology, and methods of standard economics and black political economy. Influenced by path-breaking studies presented in several scholarly economic journals, this volume is designed to provide a political-economic analysis of the past and present economic status of African Americans. The chapters in this volume represent the work of some of the nation's most distinguished scholars on the various topics presented. The individual chapters cover several well-defined areas, including black employment and unemployment, labor market discrimination, black entrepreneurship, racial economic inequality, urban revitalization, and black economic development. The book is written in a style free of the technical jargon that characterizes most economics textbooks. While the book is methodologically sophisticated, it is accessible to a wide range of students and the general public and will appeal to academicians and practitioners alike.
Google-Books-ID: itUWFxWk4OYC
Keywords: Social Science / Ethnic Studies / African American Studies; dept.soc

Juvenile delinquency - Kenty-Drane, Jessica L. (Men and masculinities: a social, cultural, and historical encyclopedia, 2004)
This reference analyzes, summarizes, and explains the complexities of men's lives and the idea of modern manhood. It looks at literature, art, and music from a gender perspective, and covers intimacy, sexual violence, pornography, sexism and rituals.
OCLC: 301173623
Keywords: dept.soc

Gender-collaborative training in elite university sport: Challenging gender essentialism through integrated training in gender-segregated sports - Ogilvie, M. F.; McCormack, Mark (International Review for the Sociology of Sport, 2020)
Competitive teamsport at university level is predominantly segregated by gender in many western countries, despite concerns that gender segregation in sport can perpetuate sexism and gender inequality. While policies and activities seek to challenge sexism and gender inequality, the use of gender collaboration within a gender-segregated system as a method to achieve this has received little attention. In this article, we draw on a year-long ethnography of elite sport and 48 in-depth interviews with elite male and female athletes at a British university to explore the impact of various forms of gender mixing during training, which we call ‘gender-collaborative training’. While men’s and women’s teams competing against each other in practice matches resulted in gender-essentialist narratives attributing difference to biology, gender-integrated practices and workouts provided opportunities for men and women to train together without the gendered sport-specific associations that can reproduce sexism. We call for gender-collaborative training to be adopted by gender-segregated teams, and suggest that where there is resistance to any integration, teams start with mixed physical workouts and progress to mixed sport-specific training and then mixed competitive training. © The Author(s) 2020.
7 citations (Crossref) [2023-10-31] WOS:000599892600001
Keywords: adult; article; dept.soc; ethnography; female; human; interview; male; narrative; peer-reviewed; sexism; training

“Dad, wash your hands”: Gender, care work, and attitudes toward risk during the COVID-19 pandemic - Umamaheswar, Janani; Tan, Catherine (Socius: Sociological Research for a Dynamic World, 2020)
Recent analyses of responses to coronavirus disease 2019 (COVID-19) have posited that men’s dismissive attitudes toward the risks of the virus reflect their attempts to conform to masculine norms that valorize bravery and strength. In this article, the authors develop an alternative account of the gender differences in attitudes toward COVID-19. Drawing on three waves of in-depth interviews with college students and members of their households (n = 45) over a period of 16 weeks (for a total of 120 interviews), the authors find that men and women in comparable circumstances perceive similar risks of COVID-19, but they diverge in their attitudes toward, and responses to, these risks. Connecting scholarship on gender and care work with research on risk, the authors argue that gender differences in attitudes toward risk are influenced by the unique and strenuous care work responsibilities generated by the COVID-19 pandemic, which are borne primarily by women—and from which men are exempt. © The Author(s) 2020.
20 citations (Crossref) [2023-10-31] tex.ids: umamaheswarDadWashYour2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85093675574 type: Article
Keywords: COVID-19; care work; dept.soc; gender; pandemic; peer-reviewed; risk perception

The impact of faith-based narratives on climate change adaptation in narikoso, fiji - Bertana, Amanda (Anthropological Forum, 2020)
Most research on climate change in South Pacific island communities has privileged people’s observations of physical environmental change with less attention paid to how people interpret the causes of these changes. Increasingly, more studies are focusing on how communities are receiving messages about environmental degradation, and from whom they are receiving them. This case study draws upon ethnographic research conducted in November 2015 in Narikoso on Ono Island in Fiji’s Kadavu Group. This village was in the process of relocating inland as a response to shoreline erosion and severe coastal flooding. By employing data drawn from interviews with government actors, religious leaders, and residents of Narikoso village along with fieldnotes from participant observation, this paper examines how village residents interpreted coastal flooding and shoreline erosion according to the biblical story of Noah’s Ark alongside a secular narrative of climate change. I conclude by showing the unique challenges these worldviews had on the community’s decision to relocate. © 2020 The University of Western Australia.
8 citations (Crossref) [2023-10-31] tex.ids: bertanaImpactFaithbasedNarratives2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092596428 type: Article
Keywords: Fiji; Relocation; climate change adaptation; dept.soc; peer-reviewed; religion; sea level rise

Policing and racial (In)Justice in the media: Newspaper portrayals of the “Black lives matter” movement - Umamaheswar, Janani (Civic Sociology, 2020)
12 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed

Family background and peer group development in a puerto rican district - Doob, Christopher Bates (Sociological Quarterly, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/098-265-729-464-977 tex.type: [object Object]
Keywords: dept.soc

Sociological aspects of alcohol and food deviations - Markham, Jean E (Annals of the New York Academy of Sciences, 1966)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-189-976-192-698 tex.type: [object Object]
Keywords: Alcoholism; Eating; Family; Human; Obesity; Sociology; alcoholism; article; dept.soc; eating; family; human; obesity; sociology

Early alcoholism treatment: The Emmanuel movement and Richard Peabody - McCarthy, K. (Journal of Studies on Alcohol, 1984)
9 citations (Crossref) [2023-10-31]
Keywords: alcoholism; central nervous system; dept.soc; diagnosis; group therapy; history; human; leisure; psychoanalysis; psychological aspect; suggestion; therapy

Psychotherapy and religion: The emmanuel movement. - Mccarthy, Katherine (Journal of Religion & Health, 1984)
This paper reconsiders the significance of the Emmanuel movement, a pre- Freudian psychotherapeutic system founded by Dr. Elwood Worcester as a method of church-sponsored healing. Its significance lies in three areas: (1) Historically, it was a popular effort by Protestant clergy to claim religious authority over psychological and psychosomatic ailments, a struggle that the medical profession eventually won almost completely. (2) The Emmanuel movement was an effort to combat the scientific materialism and medical somaticism of its time, including the excessive use of drugs. It aimed at greater individual control over emotional wellbeing through a self-help movement taught by religious leaders using some Christian ideas. Significant parallels can be found with present-day holistic health efforts. (3) Theoretically, Worcester's conception of the "person" is of interest as an effort to construct a nonreductionist view of the interactions of body, mind, and spirit. © 1984 Institutes of Religion and Health.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-717-592-132-874 tex.type: [object Object]
Keywords: dept.soc

Alternative spirituality and environmentalism - Bloch, JP (Review of Religious Research, 1998)
The relationship between religiosity and environmentalism has previously been examined by studying conservative versus liberal Christian affiliation. This study explores environmentalist attitudes amongst persons whose religiosity does not fit conventional patterns: the so-called “alternative” or “countercultural” spiritual community (e.g, New Age, Neo-Paganism). This network of individuals finds commonalty and solidarity not through organizational ties or a singular theology, but through an overriding ideology that challenges the alleged rigidity and dualistic dogma of mainstream society, and so suggests a new form of social movement. Central to this critique of the mainstream is the notion that the earth is just as sacred as the “heavens,” and so by preserving the earth, one is being “spiritual. “ Excerpts from in-depth interviews with 22 alternative spiritualists feature numerous key environmental/spiritual themes. These excerpts indicate that issues such as religiosity, “liberal” versus “conservative” affiliation, and environmental politics can take on different meanings when explored outside of mainline Christianity.
16 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000075547900004
Keywords: dept.soc

Gauging the strength of evidence prior to plea bargaining: the interpretive procedures of court-appointed defense attorneys - Emmelman, Debra S (Law and Social Inquiry-journal of The American Bar Foundation, 1997)
An important debate among court observers is whether plea bargaining undermines the ideals of justice. This article presents findings that may reconcile some inconsistent research conclusions. It describes how, prior to plea bargaining, one group of court-appointed defense attorneys gauges the strength of evidence through a tacit, taken-for-granted process that emulates trial proceedings: based on their understanding of evidence in the legal community, defenders imagine a courtroom dialogue wherein the prosecution and defense take turns presenting their cases in front of a judge and jury. At issue throughout the dialogue is whether or to what extent information is sufficient, legal, and persuasive enough to convict the defendant. Because the process is part of the defenders' ongoing and unspoken daily routines, it may elude unsuspecting investigators. Ironically, this means not only that some analysts may inappropriately conclude that legal ideals play no role in plea bargaining but also that: others may ingenuously assume that such behavior is more ethical than it actually is.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/004-264-159-069-208 tex.type: [object Object]
Keywords: dept.soc

Trial by plea bargain: Case settlement as a product of recursive decisionmaking - Emmelman, DS (Law & Society Review, 1996)
Through presentation of ethnographic research findings on court-appointed defense attorneys, this article examines plea bargaining as a component of a recursive process for deciding whether a case should be settled immediately or proceed further. The decisionmaking process has three types of activities: assessing the offer for a guilty plea, negotiating the terms of a plea bargain, and counseling the defendant and deciding on a course of action. Until a criminal case is actually settled either through a final plea agreement or a jury trial, this decisionmaking process occurs over and over again. Viewed as a component of this recursive process, plea bargaining encompasses multiple episodes of negotiating behavior as well as a wide range of formal litigation proceedings. Perhaps more important, plea bargaining and trial procedures can actually be seen to converge. I conclude that this mode of plea bargaining is not merely an effective method for representing defendants but perhaps equally or more effective than trial. Some important limitations of the findings are also discussed.
31 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1996UX39800005
Keywords: dept.soc

Stylistic sabotage and Thorstein Veblen's scientific irony - Cassano, G. (Journal of Economic Issues, 2005)
4 citations (Crossref) [2023-10-31]
Keywords: dept.soc

Book Review: corrections: A comprehensive view - Ryan, Michael (Criminal Justice Review, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/162-405-532-876-178 tex.type: [object Object]
Keywords: book.review; dept.soc

The new and improved clint eastwood: change and persistence in promise keepers self-help literature - Bloch, Jon P (Sociology of Religion, 2000)
Like other expressions of Christian conservatism, the Promise Keepers (PK) often enact complex and strained relationships between social change and social persistence. These strains are evident in the official PK literature, which employs techniques not unlike those used by mainstream pop psychology. These include the use of “scientific”-like classifications of information, authors presented as “experts” on the topic at hand, and the use of exercises to be enacted individually or in small PK discussion groups. Collectively, these strategies suggest that conservative Christians deal with many of the same complex role demands as non-conservatives. In Particular, the PK stance on gender roles, though Promoted as unambiguously “traditional” in favoring male leadership and female submission, in actuality often reflects acknowledgment and perhaps acceptance of some of the more egalitarian changes in gender role norms. Sociological implications and directions for future research are discussed.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-278-825-342-722 tex.type: [object Object]
Keywords: dept.ant; dept.soc

Identifying the involvement of multiple carnivore taxa with archaeological bone assemblages - Selvaggio, Marie M; Wilder, Joseph (Journal of Archaeological Science, 2001)
Information on the number of carnivore taxa that were involved with archaeological bone assemblages is pertinent to questions of site formation, hominid and carnivore competition for carcasses and the sequence of hominid and carnivore activity at sites. A majority of early archaeological bone assemblages bear evidence that both hominids and carnivores removed flesh and/or marrow from the bones. Whether flesh specialists (felids) or bone-crunchers (hyaenas), or both, fed upon the carcasses is crucial for deciphering the timing of hominid involvement with the assemblages. Here we present an initial attempt to differentiate the tooth mark signature inflicted on bones by a single carnivore species versus multiple carnivore taxa. Quantitative data on carnivore tooth pits, those resembling a tooth crown or a cusp, are presented for two characteristics: the area of the marks in millimetres, and the shape as determined by the ratio of the major axis to the minor axis of the mark. Tooth pits from bones modified by extant East African carnivores and latex impressions of tooth pits from extinct carnivore species are compared to those in the FLK Zinjanthropus bone assemblage. Data on tooth mark shape indicate greater variability in the Zinj sample than is exhibited by any individual extant or extinct carnivore species in the comparative sample. Data on tooth mark area demonstrate that bone density is related to the size of marks. Taken together, these data support the inference that felids defleshed bones in the Zinj assemblage and that hyaenas had final access to any grease or tissues that remained. © 2001 Academic Press.
165 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-668-240-742-014 tex.type: [object Object]
Keywords: Carnivore tooth marks; Methodology; Site formation; Taphonomy; carnivore; dept.ant; dept.soc; feeding; taphonomy; tooth

Violence in the city of women: police and batterers in bahia, brazil - Jackson, Shirley A. (American Journal of Sociology, 2009)
0 citations (Crossref) [2023-10-31] tex.eissn: 1537-5390 tex.unique-id: ISI:000265676200032
Keywords: dept.soc; peer-reviewed

A whisper toward peace: A theoretical analysis of the council for a parliament of the world religions - Bloch, Jon P (Journal for the Scientific Study of Religion, 2008)
The Council for a Parliament of the World Religions has been meeting since 1993 to foster a global religious ethic toward world peace, based on the premise that major world religions share this ethic in common. Roland Robertson's multidimensional model of globalization is utilized to analyze the Parliament's foundational Declaration, and explore why the Parliament's message is not receiving wider attention. Excerpts from anti-Parliament sources are included. Based on this analysis, the Parliament appears to have a limited conception of globalization, and so offers but a partial knowledge claim on how religion can resolve global problems. Seen in this light, it is not surprising that some oppose the Parliament's agenda, feel alienated by it, or-given its limitations-are not aware of it.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/050-703-232-358-605 tex.type: [object Object]
Keywords: dept.soc

Book Review: The path of the devil: early modern witch hunts. by gary jensen. her hidden children: the rise of wicca and paganism in america. by chas s. clifton. new age and neopagan religions in america. by sarah m. pike. witchcraft and magic: contemporary north america. edited by helen a. berger. voices from the pagan census: a national survey of witches and neo-pagans in the united states. by helen a. berger, evan a. leach, and leigh s. shaffer. researching paganisms (the pagan studies series). edited by jenny balin, douglass ezzy, and graham harvey - Bloch, Jon P. (Journal for the Scientific Study of Religion, 2008)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-902-592-460-172
Keywords: book.review; dept.soc

Cyber wars: Catholics for a free choice and the online abortion debate - Bloch, Jon P. (Review of Religious Research, 2007)
Catholics for a Free Choice (CFFC) performs considerable advocacy online, through its website as well as through press releases and interviews that appear at other sites. Opponents to CFFC also frequently post online. This article analyzes this online debate to explore how it is conceptually framed. CFFC presents a discourse that is promoted as finding ideological consistency between Catholic values and being prochoice, and which addresses a greater social good beyond the Church per se. In making these self-referential claims, CFFC could be viewed as a “community of discourse” (Wuthnow 1989) that reckons with “problems of articulation” by dealing with both specific and broader tensions. Online opponents to CFFC likewise could be viewed as communities of discourse that promote themselves as having the true Catholic values that serve the greater good. On balance, CFFC online would seem to reflect the larger quandaries of abortion discourse, whereby the Internet can offer a representative depiction of democratic free speech articulated on this controversial issue. Yet at the same time, there is little evidence to date that this online debate is changing anyone's mind or building a new consensus, despite some efforts on the part of CFFC to do so.
tex.unique-id: ISI:000252110700004
Keywords: dept.soc; ⛔ No DOI found

“When the hell are you going to grow up?”: a life-course account of hybrid masculinities among incarcerated men - Umamaheswar, Janani (Journal of Developmental and Life-Course Criminology, 2020)
Purpose: Recent life-course scholarship has argued that desistance from (rather than persistence in) crime is a marker of adulthood. In this article, I argue that a commitment to desistance is only one of many elements of the participants’ sense of adult masculinity, which is best understood by drawing on theoretical literature on “hybrid masculinities.” By linking life-course criminological literature with recent theoretical advancements in the sociology of gender, I connect two important, but as yet independent, strands of research. Methods: Using the grounded theory approach to qualitative research, I performed inductive analyses of 24 in-depth interviews with adult men incarcerated at a state-run facility in the Northeastern USA. Results: I argue that the participants construct hybrid masculinities that combine conventionally masculine traits (such as being a provider and protector) with conventionally feminine traits (such as loyalty, humility, and emotional expressiveness). These hybrid masculinities manifest through the participants’ reliance on intangible markers of adulthood, and they emerge gradually over the men’s life course. I further argue that the disruptions that incarceration poses to the men’s life course impede their ability to realize their hybrid masculinities fully. Conclusion: The current research contributes to the burgeoning literature that attempts to correct the oversimplified portrayal of incarcerated men as singularly hypermasculine, and it also highlights how incarceration disrupts men’s life course, making it difficult for them to be the “hybrid” men that they wish to be. © 2020, Springer Nature Switzerland AG.
7 citations (Crossref) [2023-10-31] tex.ids: umamaheswarWhenHellAre2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85083981410 type: Article
Keywords: Hybrid masculinity; Incarceration; Masculinity; Prison; The life course; dept.soc; peer-reviewed

“When my mother died, I think a part of me died:” maternal fusion and the relationship between incarcerated men and their mothers - Umamaheswar, J. (Journal of Family Issues, 2021)
Drawing on theoretical literature on the mothering discourse, I explore how incarcerated men give meaning to their relationships with their mothers. Using 24 in-depth interviews with incarcerated adult men, I argue that adherence to the mothering discourse results in sons holding their mothers’ maternal practices to impossibly high standards while simultaneously feeling obligated to reconcile with their mothers even when doing so is tremendously difficult. I also advance the concept of “maternal fusion”—the process through which the identities of mothers and their children are intertwined—to examine how incarcerated adult sons reproduce gendered mothering ideologies in their narratives of (a) negative early childhood and adolescent relationships with their mothers and (b) reconciliation as they reflect on their relationships with their mothers as adult sons.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089989732
Keywords: adolescent; adult; article; child; childhood; dept.soc; dept.swk; drawing; female; human; human experiment; ideology; incarceration; infant; interview; male; maternal fusion; mother; mothering; mothering discourse; narrative; peer-reviewed; theoretical study

“Changing the channel”: Hybrid masculinity in a men’s prison: - Umamaheswar, Janani (Incarceration, 2020)
Penological literature has focused extensively, and often exclusively, on the “hypermasculine” nature of men’s prisons. A separate and relatively recent body of sociological research has explored “hybrid masculinities,” whereby (usually privileged) men selectively enact traits conventionally associated with subordinate masculinities and even femininities. In this article, I draw on 24 in-depth interviews with incarcerated men to argue that these men construct hybrid masculinities in response to their feelings of insecurity and to resist the hypermasculine prison environment. In so doing, I link theoretical literature on hybrid masculinities with penological research to explore how a particularly marginalized group of men construct hybrid masculinities to cope with and challenge hegemonic masculinity in prison.
7 citations (Crossref) [2023-10-31] tex.ids: umamaheswarChangingChannelHybridforthcoming
Keywords: Incarceration; dept.soc; gender; hybrid masculinities; peer-reviewed; prison masculinity; prisons

Book Review: Black Woman’s Burden: Commodifying Black Reproduction - Jackson, Shirley A. (Contemporary Sociology, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000284818800053, lens.org/019-048-940-787-433, lens.org/122-733-001-266-479, pop00332 tex.type: [object Object] tex.unique-id: [object Object]
Keywords: book.review; dept.soc

Backlash 9/11: middle eastern and muslim americans respond - Woods, David W. (Mobilization, 2011)
tex.unique-id: ISI:000292423800012
Keywords: dept.soc; ⛔ No DOI found

Book Review: women: judith schoenen, das image der frau — wege zu einem neuen selbstbild [A woman’s image — path to a new Self-Portrait]. opladen and farmington hills, MI: barbara budrich, 2008, 172 pp., ISBN 9783866491007, 12.90 - Eich-Krohm, Astrid (International Sociology, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00369 tex.type: [object Object]
Keywords: book.review; dept.soc

The CDU and the politics of gender in germany: bringing women to the party - Eich-Krohm, Astrid (Gender & Society, 2012)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000304200500012
Keywords: dept.soc

Is Fifty Really the New Thirty? The Stigma of Age as a Form of Strain and its Role in Drug and Alcohol Abuse and Dependence by Women - Black, Pamela; Brown, Alan D. (Deviant Behavior, 2016)
Aging bodies stigmatize women. The effects of stigma, health issues, goal disappointment, and a combination of age and minority group status, overwhelm older women's coping strategies, leading to maladaptive behaviors. General strain theory posits a relationship between negative stimuli and deviant behavior. Advancing age and age-related stigma reflect this strain. This study explores the relationship between strain and substance abuse or dependence, comparing subsamples of middle age (35- to 49-year-old women) and older middle age (50- to 64-year-old) women. Data suggest that minority age status coupled with acute or mental health issues increase substance abuse or dependence by older women.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-113-646-643-985 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.soc

Organizing lesbian/queer bathhouse events: Emerging forms of sexual experience. - Brown, A D; Gailey, Nerissa (Journal of Lesbian Studies, 2016)
Discussions of public sexual spaces in the social science literature have, until recently, been dominated by analyses of men's use of these spaces for erotic expression. In the late 1990s, feminist collectives began to explore the emancipatory potentials these spaces can have for lesbian sexualities. After a police raid on one such event called the "Pussy Palace," scholars in diverse disciplines began to explore how these events have both opened up and restricted erotic possibilities for lesbians, queer women, and trans* attendees. This article reviews the existing social science literature on lesbian and queer bathhouse events and highlights several key themes and subthemes that have dominated the discourse, including the importance that these spaces be recognized for their ability to both shape and be shaped by principles of community, safety, and sexual health/wellness.
3 citations (Crossref) [2023-10-31] Place: England Brown, A D. a Department of Sociology, Southern Connecticut State University, New Haven, Connecticut, USA. Gailey, Nerissa. b Department of Sociology and Anthropology, Mount Saint Vincent University, Halifax, Nova Scotia, Canada.
Keywords: *Homosexuality; Female; *Homosexuality; Male; *Public Facilities; *Sexual Behavior; Baths; Female; Homosexuality; Female; Homosexuality; Male; Humans; Lesbian; Male; Public Facilities; Sexual Behavior; Social Behavior; bath; bathhouse; dept.soc; ethic of care; female; human; lesbianism; male; male homosexuality; public sex; sanitation; sexual behavior; sexual politics; social behavior

Beyond either/or: Reading trans* lesbian identities. - Gailey, Nerissa; Brown, A D (Journal of Lesbian Studies, 2016)
Previous research has explored the affiliation and distancing strategies employed in published memoirs of gender transition. In this article, we are particularly interested in elucidating the ways in which individuals construct identities and characterize their sexualities, and how sociohistorical constraints might influence what is expressed with respect to this in personal narratives of transition. Using the memoirs of Lili Elbe (Hoyer, 1933) and Joy Ladin (2013) as conceptual brackets, this article investigates the complex relationship between the development and articulation of trans* identities and lesbian sexualities within the context of published memoirs of gender transition.
3 citations (Crossref) [2023-10-31] Place: England Gailey, Nerissa. a Carleton University, Ottawa, Ontario, Canada. Brown, A D. b Southern Connecticut State University, New Haven, Connecticut, USA.
Keywords: *Homosexuality; Female/px [Psychology]; *Transgender Persons/px [Psychology]; Female; Gender Identity; Homosexuality; Female; Humans; Lesbian; Male; Personal Narratives as Topic; Sex Reassignment Surgery; Sex Reassignment Surgery/px [Psychology]; Transgender Persons; Women's Rights; dept.soc; female; feminist movements; gender identity; human; identity; lesbianism; literature; male; memoirs; psychology; sex reassignment; sexuality; trans*; transgender; women's rights

“A grain of salt in a pepper shaker”: interviewing whites, blacks, and latinos about their neighborhood preferences - Meyerhoffer, Cassi A (Sociological Forum, 2016)
Several perspectives dominate as explanations for neighborhood preferences: pure race, racial proxy, race-based neighborhood stereotyping, and race-associated neighborhood factors. This analysis extends and supports the pure race and race-associated neighborhood factors arguments by showing that these theories are applied differently depending on respondents' social class, race and ethnicity, and whether they are talking about white, black, or Latino neighborhoods. Race-associated factors are emphasized for white and black neighborhoods, but pure race serves as a better theoretical framework for understanding people's preferences for Latino neighborhoods. I analyze qualitative interview data, using maps of real neighborhoods and hypothetical neighborhood show cards, to examine the neighborhood preferences of 65 white, black, and Latino residents in Ogden, Utah, and Buffalo, New York.
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000383624000002, lens.org/083-894-188-392-591 tex.type: [object Object]
Keywords: African Americans; Latinos; dept.soc; neighborhood racial association; pure race; racial proxy; racial residential segregation

"I have more in common with Americans than I do with illegal aliens" culture, perceived threat, and neighborhood preferences - Meyerhoffer, Cassi A (The Sociology of Race and Ethnicity, 2015)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-309-053-002-109 tex.type: [object Object]
Keywords: dept.soc

Book Review: social order and the fear of crime in contemporary times, by stephen farrall, jonathan jackson, and emily gray. new york, NY: oxford university press, 2009. 319pp. 100.00 cloth. ISBN: 9780199540815 - Adams, Gregory (Contemporary Sociology, 2011)
Citation Key Alias: pop00326 tex.type: [object Object]
Keywords: book.review; dept.soc; ⛔ No DOI found

Social order and the fear of crime in contemporary times - Adams, Gregory (Contemporary Sociology-a Journal of Reviews, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-967-693-481-198 tex.unique-id: [object Object]
Keywords: dept.soc

Principles of racial integration vs. perceptions of non-White neighborhoods: Comparing hypothetical and real neighborhood choice - Meyerhoffer, Cassi A.; Kenty-Drane, Jessica (Journal of Urban Affairs, 2019)
Using qualitative interview data, we examine the consistency of White residents' responses to questions about their preferences for the racial composition of their neighborhoods when comparing hypothetical showcards and maps of real neighborhoods in respondents' cities. This approach allows for an examination of how residents' preferences for real neighborhoods align with preferences for idealized neighborhoods and the explanations people give when describing their preferences for neighborhoods of color. Data come from qualitative interviews conducted in Buffalo, New York, and Ogden, Utah.
3 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000481781200007, lens.org/130-645-906-313-241 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: Buffalo; New York [New York (STT)]; New York [United States]; Ogden; United States; Utah; data set; dept.soc; neighborhood; peer-reviewed; perception; qualitative analysis; racial disparity; racial segregation

All is quiet on the Russian front: ceasefires and the pursuit of legitimacy by self-proclaimed “republics” in Ukraine - Lennon, Olena; Adams, Gregory (Eurasian Geography and Economics, 2019)
This paper examines the pursuit of legitimacy by the self-proclaimed “republics” in Ukraine. While these “republics” are illegal, questions of their legitimacy are commonly discussed almost entirely through Weberian rule-conformity. We argue that this one-dimensional view of legitimacy overlooks the rich context of normative aspects of power relationships. If the occupied Donbas is to be reintegrated into Ukraine, it is essential to understand the perceived legitimation of the political institutions in this region. We use David Beetham’s framework of legitimacy—consisting of legality, morality, and consent—to analyze the “republics’” pursuit of legitimacy. Our analysis leads to the proposition that while the “republics” are illegal, their supporters’ normative perceptions of the right to govern have ascribed more validity to the fake “governments” than what would have been expected from a legal point of view. Additionally, while a ceasefire between the Russian proxies and Ukraine’s forces has reduced violence, it has also levied temporal effect on the legitimation of illegitimate institutions. Our treatment of the process of legitimation over time helps us identify potential strategies of delegitimization should DPR and LPR reincorporate with Ukraine-controlled territory. Without dismantling internal perceptions of institutional legitimacy among inhabitants of nongovernment-controlled areas, a re-integration could not be accomplished.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-456-632-625-995, pop00296 tex.type: [object Object]
Keywords: Russia; Ukraine; conflict management; de facto states; dept.soc; institutional framework; legislation; legitimacy; peer-reviewed; political conflict; political power; reconciliation; secessionism; separatism

Understanding the potential of state-based public health genomics programs to mitigate disparities in access to clinical genetic services - Senier, Laura; Tan, Catherine; Smollin, Leandra; Lee, Rachael (Genetics in Medicine, 2019)
7 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed

The yoke of childhood - Misgivings about children's relationship to technology in contemporary science fiction - Kenty-Drane, Jessica L. (Child and youth agency in science fiction: travel, technology, time, 2019)
Keywords: dept.soc; faculty_collection

A life-course perspective on incarcerated women’s views on adulthood - Umamaheswar, Janani (Women & Criminal Justice, 2018)
2 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed

Studying homeless and incarcerated persons: A comparative account of doing field research with hard-to-reach populations - Umamaheswar, Janani (Forum Qualitative Sozialforschung, 2018)
In this article, I discuss the process of conducting research with two vulnerable and hard-to-reach populations (homeless and incarcerated men) in three research locations characterized by varying levels of gatekeeping: a prison, public streets in an urban city, and a residential facility for homeless men. I argue that, despite the obstacles to independent research that gatekeepers (officials who can grant or deny researchers access to participants) pose, research with vulnerable, hard-to-reach populations in different field sites reveals some of the benefits of using field sites characterized by gatekeeping and strict rules to which researchers must adhere. Many of these benefits, however, go unacknowledged in discussions of access in qualitative studies—especially in the penological literature. I conclude that, instead of shying away from qualitative prison studies, researchers should take advantage of the benefits that prisons offer as field sites.
Citation Key Alias: lens.org/135-139-935-744-665, pop00300
Keywords: Access; Feldforschung; Field research; Gatekeeping; Gefängnis; Gefängnisforschung; Grounded theory methodology; Grounded-Theory-Methodologie; Homelessness; Interviewing; Interviews; Obdachlosigkeit; Prison; Prison research; Zugang; access; dept.soc; field research; gatekeeping; grounded theory methodology; homelessness; interviewing; peer-reviewed; prison; prison research

Book Review: 'Connecting in college: How friendship networks matter for academic and social success' by J. M. McCabe - Kenty-Drane, Jessica L. (American Journal of Sociology, 2018)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000434407000030 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: book.review; dept.soc; peer-reviewed

Navigating the evidentiary turn in public health: Sensemaking strategies to integrate genomics into state-level chronic disease prevention programs - Senier, Laura; Smollin, Leandra; Lee, Rachael; Nicoll, Lauren; Shields, Michael; Tan, Catherine (Social Science & Medicine, 2018)
1 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed

“I'm a normal autistic person, not an abnormal neurotypical”: Autism Spectrum Disorder diagnosis as biographical illumination - Tan, Catherine D. (Social Science & Medicine, 2018)
40 citations (Crossref) [2023-10-31]
Keywords: dept.soc; peer-reviewed